Microbial involvement in iodine cycle: mechanisms and potential applications - Duborská, Eva; Vojtková, Hana; Matulová, Michaela; Šeda, Martin; Matúš, Peter (Frontiers in Bioengineering and Biotechnology, 2023)
Stable iodine isotopes are essential for humans as they are, necessary forto producinge thyroid gland hormones of thyroid gland. However, there are hazardous radioactive iodine isotopes that are emitted into the environment through radioactive waste produced generated by nuclear power plants, nuclear weapon tests, and medical practice. Due to the biophillicbiophilic character of iodine radionuclides and their enormous biomagnification potential, their elimination from contaminated environments is essential to prevent the spread of radioactive pollution in ecosystems. Since microorganisms play a vital role in controlling iodine cycling and fate in the environment, they also can be efficiently utilized in solving the issue of contamination spread. Thus, this paper summarizes all known on microbial processes that are involved in iodine transformation to highlight their prospects in remediation of the sites contaminated with radioactive iodine isotopes.Determining iodine species in surface waters poses a significant challenge; iodate (IO3 -) is noted as the prevailing species, which can undergo microbially mediated reduction (Zaruba et al., 2017;Wadley et al., 2020). The exact mechanism of iodate reduction is still unclear; however, available data suggest that it is mediated by microorganisms via enzymatic transformations and